2012
DOI: 10.1542/peds.2011-1545
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Characteristics Associated With Abusive and Nonabusive Head Trauma: A Systematic Review

Abstract: Clinical and radiographic characteristics associated with AHT and nAHT were identified, despite limitations in the literature. This systematic review also highlights the need for consistent criteria in identifying and reporting clinical and radiographic characteristics associated with AHT and nAHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
1
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(134 citation statements)
references
References 46 publications
10
111
1
12
Order By: Relevance
“…69,132 Compared with children with severe accidental trauma, children with AHT are more likely to have subdural hemorrhage, retinal hemorrhages, and associated cutaneous, skeletal, and visceral injuries. 97,[133][134][135][136] Inflicted injuries tend to occur in younger patients and result in higher mortality and longer hospital stays than does accidental head trauma. 97,129,137 Infants with intracranial injuries may have no neurologic symptoms and are sometimes identified during a medical evaluation for other suspicious injuries.…”
Section: Head Injuriesmentioning
confidence: 99%
“…69,132 Compared with children with severe accidental trauma, children with AHT are more likely to have subdural hemorrhage, retinal hemorrhages, and associated cutaneous, skeletal, and visceral injuries. 97,[133][134][135][136] Inflicted injuries tend to occur in younger patients and result in higher mortality and longer hospital stays than does accidental head trauma. 97,129,137 Infants with intracranial injuries may have no neurologic symptoms and are sometimes identified during a medical evaluation for other suspicious injuries.…”
Section: Head Injuriesmentioning
confidence: 99%
“…SS was rated necessary in all clinical scenarios involving SDHs but not in all scenarios involving EDHs, which have been associated with a lower risk of abuse. 21,22 In addition, SS was not deemed necessary when a tiny extra-axial hemorrhage directly under a skull fracture was found in children 12 to 23 months old with a history of trauma and infants 6 to 11 months old with a history of a high fall (≥3 feet). Panelists had specifically requested the addition of scenarios specifying a tiny extraaxial hemorrhage under a skull fracture, as this injury was thought to be consistent with a direct impact mechanism, such as a fall, and of less concern for abuse than larger SDHs.…”
Section: Discussionmentioning
confidence: 99%
“…SS was deemed universally necessary in children <6 months old, likely because they are much less likely than older infants and toddlers to suffer from accidental ICH due to their lack of independent mobility. 21 Nonetheless, universal evaluation in these populations is not the norm, which may contribute to missed opportunities to diagnose AHT. 7,11 Studies have shown that age-and injury-specific clinical guidelines regarding SS use have the potential to eliminate disparities in evaluation and improve abuse detection.…”
Section: Discussionmentioning
confidence: 99%
“…Although some children with isolated skull fractures may require hospital admission for on-going symptoms or evaluation of nonaccidental trauma, [15][16][17][18] outpatient care with close follow-up is a safe option for many. 10 At our study institution, the baseline hospitalization rate for children with isolated skull fractures was similar to the national average.…”
Section: Methodsmentioning
confidence: 99%